Determinants, characteristics and treatment of neck pain in a tertiary care hospital in Kerala - Joseph, Liya Roslin (International Journal of Basic & Clinical Pharmacology, 2016)
Background: This study was undertaken to study the determinants, clinical characteristics and treatment pattern of neck pain in patients attending outpatient department of Physical medicine and Rehabilitation in a tertiary care hospital. Methods: Study comprehended single patient visit. Data regarding patient demographics, characteristics of neck pain and clinical diagnosis, drugs prescribed to each patient were recorded in a pre prepared proforma. Clinician’s opinion about patient’s X-ray of cervical spine and the data regarding alternative treatment modalities were also noted. Data analysis was done with the help of excel 2007 and SPSS 16 statistical software. Results: Among 170 patients included in the study 38.8% of patients were in the age group of 40-49 years with M:F ratio-1:2.9. 98.8% of patients experienced radiation of neck pain to one or both arms. Neck pain also was associated with numbness in arm (82.4%), forearm (61.8%) or hand (59.4%) and neck stiffness (99.4%). Half of the study population were found to have neurological deficit. 98.2% of patients had positive radiological evidence for neck pain. Cervical spondylosis (85.9%) was the most commonly observed cause for neck pain. All patients received pharmacotherapy with NSAIDS and muscle relaxants. Diclofenac was the most commonly prescribed NSAID. 45% of the patients received alternative and complementary treatments for neck pain. Conclusions: NSAIDs and central skeletal muscle relaxants are the commonly prescribed medications and alternative treatments like spinal manipulation and physiotherapy appears to be beneficial in patients with neck pain.